INSILICO CHARACTERISATION OF PROTEINS OF SALVINIA MOLESTA D.S.MITCHELL AN AQUATIC WEED AND ASSESSMENT OF NANOPARTICLE SYNTHESISING ABILITY OF CLOSELY RELATED PLANT SPECIES - T. G. NITHYA; SWETHA K; JAYANTHI J; RAGUNATHAN MG (International Journal of Pharma and Bio Sciences, 2016)
The main aim of the study is to analyse the proteins of Salvinia molesta using various bioinformatics tools.The proteins were structurally as well as functionally characterized using tools like protparam,SOPMA and SOSUI. NAD(P)H quinone oxidoreductase protein in Salvinia molesta was selected for evaluation and protein BLAST was performed.Primary structure prediction were performed to evaluate physical and chemical characteristics of proteins viz.,Molecular weight, pI etc.The secondary structures like alpha helix, beta turns etc.,were studied.Transmembrane protein was identified and analysed.NAD(P)Hquinone oxidoreductase possess the abilty to reduce metals and hence Salvinia molesta was predicted for its ability to synthesis nanoparticles.Finally, phylogenetic analysis was carried out using NJ plot.Phylogenetic tree revealed the closeness of Salvinia molesta with plants like Azolla caroliniana, Lygodium japonicum etc.,revealing the efficacy of these plants also in synthesising nanoparticles.